Die vraag na norme vir moraliteit - Heyns, Johan Adam (Verbum et ecclesia, 1989)
The demand for norms for morality This article is a short investigation of the existence and the character of norms for morality. Owing to the secularized society in which we live today the well known Martin Buber once spoke of the eclipse of the light of heaven as an eclipse of God and, we may add, an eclipse also of moral norms. A theocentric basis for moral norms should be accepted as well as the fact that the whole of creation is subject unconditionally to his cosmonomic order. Consequently there is a concrete demand or claim on man in the situation he confronts, which cannot be reduced to an application of general moral norms to the situation concerned. God does speak to us through historical situations as well. We shall have to judge the concrete historical situation in its immediate hic et nunc call on us in the light of the will and law of God, as they are revealed to us in his Word.